Sosialisasi Peningkatan Kualitas Pelayanan Pada Usaha UMKM Rumah Makan Nasi Padang Etek Yet di Dempo Raya - Sari, Yetri Oktiva; Effendi, Yanto (Jurnal Dehasen Mengabdi, 2023)
This study aims to analyze the role of socialization in improving the service quality of Micro, Small, and Medium Enterprises UMKM at "Rumah Makan Nasi Padang Etek Yet" in Dempo Raya. A qualitative approach was employed, collecting data through observation, interviews, and documentary analysis. The results of the study indicate that socialization has a positive impact on creating an understanding of service standards and strengthening the positive interaction between employees and customers. Effective socialization contributes to an increase in customer satisfaction and supports the growth of UMKM.